2022
DOI: 10.1080/21645515.2022.2155390
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of hepatitis B vaccination in preterm birth and low birth weight infants born to hepatitis B surface antigen-positive mothers: Time to close the policy-practice gap

Abstract: National Immunization Program-version 2016 (ISIV-NIP-v2016) recommended a 4-dose hepatitis B vaccine (HepB) schedule for preterm birth (PTB) and low birth weight (LBW) infants born to HBsAg-positive mothers. However, the implementation of this immunization strategy in the past five years has not been fully evaluated in China. We reviewed the data of pregnant women and live-born infants from 24 hospitals between 2016 and 2021 in Lu’an, Anhui province, to estimate the prevalence of PTB, LBW, and hepatitis B viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…When analysing the reasons for blood donation delays, the study found that the majority of cases were due to temporary postponement reasons, accounting for 97.75% of the total delay. As China’s national immunisation and voluntary blood donation programmes have developed extensively, the likelihood of blood transfusion-related infections such as hepatitis B has decreased significantly among the population, especially among students who have undergone comprehensive immunisation programmes ( 16 , 17 ). In addition, repeated screening during the blood donation process has led to the exclusion of a large number of donors with infectious diseases such as hepatitis B and syphilis ( 18 ), which is one of the reasons for the decreasing proportion of permanent deferrals over the years.…”
Section: Discussionmentioning
confidence: 99%
“…When analysing the reasons for blood donation delays, the study found that the majority of cases were due to temporary postponement reasons, accounting for 97.75% of the total delay. As China’s national immunisation and voluntary blood donation programmes have developed extensively, the likelihood of blood transfusion-related infections such as hepatitis B has decreased significantly among the population, especially among students who have undergone comprehensive immunisation programmes ( 16 , 17 ). In addition, repeated screening during the blood donation process has led to the exclusion of a large number of donors with infectious diseases such as hepatitis B and syphilis ( 18 ), which is one of the reasons for the decreasing proportion of permanent deferrals over the years.…”
Section: Discussionmentioning
confidence: 99%
“…The enrolment strategy of this study was divided into two stages. In the first stage, we screened eligible PTB children at 24 major delivery hospitals in Lu'an, China, as reported in our previous study 21 . In total, we screened 1077 PTB children born in 2016.…”
Section: Methodsmentioning
confidence: 99%
“…Studija Qin i saradnika je pokazala da je stopa pravovremene vakcinacije protiv hepatitisa B za prevremeno rođenu decu i novorođenčad sa malom porođajnom težinom u 24 bolnice u provinciji Anhui u Kini, od 2016. do 2021.g. bila samo 78,59% (17). Rezultati istraživanja Jacobson i saradnika pokazuju da više od 50% prevremeno rođene dece u državi Washington, SAD, još uvek nije dovoljno vakcinisano u uzrastu od 19 meseci, a jedna trećina prevremeno rođene dece još uvek nije primila vakcinu nakon 36 meseci (18).…”
unclassified